Developing Marketing Strategy for User-Generated Content: Study Case for Company X - Imanulrachman, Akbar (Jurnal Indonesia Sosial Sains, 2024)
This study investigates strategies to enhance user-generated content (UGC) growth for Company X, a part of Company X, to address the declining trend in UGC contributions and increasing operational costs. The study employs a qualitative methodology, including in-depth interviews with Company X users and content creators, to identify user personas, motivations, and preferences. External analyses such as PESTEL, competitive analysis, and internal SWOT analysis are used to frame the problem. The results suggest that enhancing the reward system, aligning incentives with user expectations, and improving platform engagement can increase UGC contributions. The proposed strategies aim to leverage UGC to reduce costs and boost user engagement and retention, supporting Company X’s future growth.